An Analysis of Subjectum Litis and Objectum Litis on Dispute about the Authority of State Institution from the Verdicts of the Constitutional Court - Triningsih, Anna; Mardiya, Nuzul Qur’aini (Constitutional Review, 2017)
The relationship of mutual control and balance between state institutions gives an opportunity for the emergence of the dispute about the authority of state institutions, especially the dispute about the constitutional authority. In relation to a dispute about authority of state institutions given by the 1945 constitution, a judicial institution is used to resolve the dispute. That judicial institution is the Constitutional Court. The court can evaluate the subjectum litis and objectum litis from the dispute about the authority of state institutions. Therefore that matter will be resolved definitively by the verdict of the Constitutional Court where the verdict is permanent and binding, then later it will become a jurisprudence, and it will be used as a reference. There are eight verdicts of the Constitutional Court related to disputes about the authority of state institutions which are related to the subjectum litis and objectum litis, such as: The verdict of The Consitutional Court No.004/SKLN-IV/2006; the verdict of the Consitutional Court No.030/SKLN-IV/2006; the verdict of the Consitutional Court No. 26/SKLN-V/2007; the verdict of the Consitutional Court No. 27/SKLN-VI/2008; the verdict of the Consitutional Court No. 1/SKLN-VIII/2010; the verdict of the Consitutional Court No. 2/SKLN-IX/2011; the verdict of the Consitutional Court No. 5/SKLN-IX/2011; and the verdict of the Consitutional Court No. 2/SKLN-X/2012.